Penerapan Metode Diskusi Kelompok Untuk Peningkatan Hasil Belajar PAI Siswa Kelas XI F 10 SMAN 8 Padang - Ulfa, Rahmania (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to improve students' learning outcomes through the implementation of the Group Discussion method in the subject of Strengthening Faith with the Virtue of Sincerity in class XI F 10 at SMA Negeri 8 Padang. The research was conducted in two cycles using a Classroom Action Research (CAR) approach. The results showed that in cycle I, 50% of the students achieved the Minimum Completeness Criteria (KKTP), while in cycle II, the number of students who completed the task increased to 75%. The implementation of the Group Discussion method with the aid of interactive presentation media, such as PowerPoint, proved effective in enhancing students' understanding and involvement. Although students' learning outcomes in cycle II have improved, some students still did not achieve KKTP, so this research will continue to cycle III to reach more optimal results.